KOMPONEN DAN MODEL PENGEMBANGAN KURIKULUM - Achruh, Andi (Inspiratif Pendidikan, 2019)
The curriculum as an educational design has a very strategic position in all aspects of educational activities. Considering the importance of curriculum development in education, the preparation must refer to a solid and strong foundation. The foundation of curriculum development is not only needed for the compilers of the curriculum (macro) or the written curriculum which is often referred to as the ideal curriculum, but must also be understood and used as a basis for consideration by the implementers of the (micro) curriculum, namely the education supervisors and the teachers and parties - other parties related to the tasks of managing education, as material to be used as instruments in conducting coaching towards the implementation of the curriculum at each type and level of education. With this important position, curriculum development cannot be done arbitrarily, but it must be based on various considerations, or a foundation so that it can be used as a foothold in organizing the educational process, so as to facilitate the achievement of educational and learning goals more efficiently and effectively.